The Definitive Guide to Apache MyFaces and Facelets - Marinschek, Martin; Wadia, Zubin; Saleh, Hazem; Byrne, Dennis; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2008)
The Definitive Guide to Apache MyFaces and Facelets is an ideal reference if you're looking to develop real–world applications with the open-source lightweight Apache MyFaces and Dojo (the Ajax API). The book focuses less on theory and more on aspects like scalability, design, optimization, and configuration. This book emphasizes meeting real–world requirements for performance and scalability. It includes lucid code samples that reflect the pattern being described. The “In the Trenches” sections in each chapter give you advice and recommendations based on actual experiences with each pattern. What's more, the “Extreme Extensions” section at the end of each relevant chapter is dedicated to a “freestyle” expression of taking a particular pattern or set of patterns to the max. (This is a great way for you to learn because of the magnification effect.) This is also the first book to embrace the Dojo framework for Ajax.
An Introduction to JavaServer Faces -- The Tomahawk Project -- Facelets -- The Trinidad Project -- Conversations and Scoping with Orchestra -- Layouts and Themes with Tobago -- Antipatterns and Pitfalls.
Keywords: Open source software; Computer programming; Software engineering; Open Source; Software Engineering/Programming and Operating Systems